Fractional Carbon Dioxide Laser Technique Versus Derma Roller Therapy in Patients with Post-Acne Scars - Mayank Kaushik (Asian Journal of Medical Research, 2021)
Background: Acne vulgaris is a common skin disease presenting as non-inflammatory lesions, inflammatory lesions and varying degrees of scarring, affecting mostly the face but also the back and chest. The present study compared fractional carbon dioxide (CO2) laser technique (FCLT) versus derma roller therapy (DT) in patients with post-acne scars. Subjects and Methods: 56 patients with post-acne scars of both genders were classified into 2 groups of 28 each. Group I patients was treated with derma roller therapy and the other group was treated with fractional CO2 laser every 4 weeks over a period of 24 weeks. An objective and subjective baseline assessment was done for each patient using global acne scarring classification. Results: Response was satisfactory seen in 7 in group I and 2 in group II, good in 8 and 10, very good in 10 and 12 and excellent in 3 and 4 in group I and II respectively. The mean objective score at baseline in group I was 29.5 and at follow up was 16.5 and in group II at baseline was 29.8 and at follow up was 15.2. The difference was significant (P< 0.05). Conclusion: Both the modalities were found to be equally efficacious in management of post acne scars.